Anne Birrell (trad.) New Songs from a Jade Terrace: An Anthology of Early Chinese Love Poetry, Londres, George Allen y Unwin, 1982, pp. xxx-374. - Maeth Ch., Russell (Estudios de Asia y África, 1984)
-